New advances in science mapping and performance analysis of the open innovation and tourism relationship - Beatriz Mota; Orlando Lima Rua; Isabel Neira-Gómez (Journal of Open Innovation: Technology, Market and Complexity, 2024)
The number of scientific publications studying open innovation (OI) and tourism has increased since the first concept appeared. Nevertheless, there is still a gap regarding the science mapping and performance analysis of these two concepts. Although there are studies that focus on open innovation and tourism, few are studying the relationship between themes. We aimed to address this gap by reviewing the literature and searching the Scopus database using R. Bibliometrix. We identified 45 published articles between 2010 and 2022, covering 23 sources and 130 authors. The results indicate a strong collaboration network among authors. Open Innovation, Tourism, and Sustainability are the trend topics, as well as the three main keywords. The emerging topics are “open innovation in tourism”, “service innovation” and “overtourism”. Keywords, trend topics, and emerging topics can be valuable guides for researchers and help them decide which path to take in their studies in this field. This paper is a starting point for carrying out further research that relates OI to other areas of tourism, such as smart tourism or smart tourism destinations, which are highlighted in some of the most recent articles that were under this study.